Clinical Significance and Prognostic Value of the Maximum Standardized Uptake Value of 18F-Flurodeoxyglucose Positron Emission Tomography–Computed Tomography in Colorectal Cancer - Yin, Yi-xin; Xie, Ming-zhi; Liang, Xin-qiang; Ye, Meng-ling; Li, Ji-lin; Hu, Bang-li (Frontiers in Oncology, 2021)
Background: The role of 18F-flurodeoxyglucose (18F-FDG) PET/CT in colorectal cancer (CRC) remains need to clarify. This study aimed to explore the association of SUVmax, a parameter of 18F-FDG, with KRAS mutation and Ki-67 index, and the survival in CRC patients. Methods: Data of sixty-six CRC patients underwent 18F-FDG PET/CT scan was included. The clinical significance of SUVmax in CRC was analyzed, and the association of SUVmax with KRAS mutation and Ki-67 index were determined. A meta-analysis was conducted by combing the published data and this study, then the association of SUVmax with KRAS mutation, Ki-67 index, and the prognostic value was also determined. Results: By analyzing the data of 66 CRC patients, SUVmax was not related to TNM stage, clinical stage, gender, KRAS mutation, but related to the tumor location and nerve invasion. SUVmax has no significant correlation with the tumor biomarkers and Ki-67 index. Data of seventeen studies indicated that SUVmax was significantly increased in mutated type compared with wild type of KRAS in CRC; four studies showed that there was no remarkable difference between patients at high and low Ki-67 index regarding the SUVmax; Twelve studies revealed that SUVmax has no significant association with the overall survival and disease-free survival in CRC patients, respectively. Conclusions: Base on the combine data, this study demonstrated that SUVmax of 18FDG-PET/CT was different in colon and rectal cancer, and associated with the KRAS mutation, but not the Ki-67 index; there was no significant association of SUVmax with the survival of CRC patient.